Design, syntheses, and characterization of new thermoplastic polyureas based on 3,4-ethylenedioxythiophene - Ojha, U. P.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
New thermoplastic polyureas labeled PUn (n = 2, 3, 4, 6, 7, 9, or 10), based on 3,4-ethylenedioxythiophene (EDOT) with flexible aliphatic spacers, were synthesized and characterized for the first time. EDOT was chosen as a replacement for the aromatic phenyl group in conventional thermoplastics based on urea linkages to improve solubility without compromising the thermal properties. As synthesized, all the samples exhibited a semicrystalline nature. The glass-transition and melting temperatures showed a strong dependence on the spacer length. A comparison of the thermal properties of these polyureas with the corresponding phenyl analogues indicated that EDOT was a viable heteroatomic analogue of the phenyl group to be inserted into the main-chain polyureas without hampering their thermal stability. The polyureas with spacer lengths greater than hexamethylene formed transparent gels in N-methylpyrrolidone, 1,1,2,2-tetrachloroethane, and dimethyl sulfoxide. The molecular packing of the polyureas was assigned with wide-angle X-ray diffraction studies. (c) 2005 Wiley Periodicals, Inc.
Keywords: 3; 4-ethylenedioxythiophene; heteroaromatic polymers; Polyurea; polyurea gels; Thermogravimetric analysis (TGA); thermoplastics; WAXS

Pyridine mediated supramolecular assemblies of 3,5-dinitro substituted benzoic acid, benzamide and benzonitrile - Arora, KK; PrakashaReddy, J; Pedireddi, VR (Tetrahedron, 2005)
Synthesis and characterization of molecular assemblies of pyridine adducts, la, 2a and 3a, of 3,5-dinitrobenzoic acid, 1, 3,5-dinitrobenzamide, 2 and 3,5-dinitrobenzonitrile, 3, respectively, have been reported. All these adducts were obtained by crystallization of 1, 2 and 3 from pyridine. However, crystallization of I from pyridine in the presence of benzene resulted in the formation of a pyridinium adduct, 1b, along with a water molecule. All the adducts crystallize in a 1: 1 molecular ratio except la, which forms a 1:2 adduct, as characterized by single crystal X-ray diffraction method. The adducts crystallize in different space groups-la, orthorhombic, Pna2(1); 1b, monoclinic, P2(1); 2a, monoclinc, C2/c; 3a, triclinic, P-1. In two-dimensional arrangement, la, 1b and 3a form sheet structures. In la, within the two-dimensional sheets, large cavities are formed, which are occupied by pyridine molecules. In 1b, the sheets are catenated to form a chicken-wire network. However, 2a formed a crossed ribbon packing pattern with empty channels in the three-dimensional structure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 3; 5-dinitrobenzamide; 5-dinitrobenzoic acid; 5-dinitrobenzonitrile; channel structures; host-guest complexes; layered structures; molecular recognition; Pyridine

General strategy for a short and efficient synthesis of 3-hydroxy-4-methylprolines (HMP) - Mohapatra, Debendra K.; Mondal, Dhananjoy; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The non-proteinogenic amino acid 3-hydroxy-4-methylproline (HMP) is an active constituent of some potent antimicrobials including echinocandins, nostopeptins, pneumocandins, sporiofungin and mulundocandins. A synthesis has been achieved in 10 steps with 29% overall yield; the Evans' aldol reaction using Crimmins' modified method was pivotal to the success of the strategy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 3; 4-disubstituted proline; Crimmins' aldol reaction; Garner's aldehyde; non-proteinogenic amino acids; RUO4 mediated oxidation

N,N `,N `'-Tri-Boc-guanidine (TBG): a common starting material for both N-alkyl guanidines and amidinoureas - Prabhakaran, Panchami; Sanjayan, Gangadhar J. (Tetrahedron Letter, 2007)
{In this Letter, we describe the unexpected reaction pattern of N,N',N''
Keywords: 1-substituted-1H-1; 2; 3; 4-tetrazoles; Ionic liquid; sodium azide; substituted amine; triethyl orthoformate

Short enantioselective synthesis of (+)-L-733,060 via Shi epoxidation of a homoallylic carboxylate - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and efficient enantioselective synthesis of (+)-L-733,060 in 92% ee via Shi epoxidation of a homoallylic carboxylate is described. Johnson-Claisen rearrangement was employed to obtain the required carbon backbone, whilst intramolecular reductive O-to-N-ring expansion of a delta-azidolactone was used in the construction of the piperidine moiety. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-aminoalcohols; 3; 3-sigmatropic rearrangement; asymmetric epoxidation; Lactone

Use of the pictet-spengler reaction for the synthesis of 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines and 1,4-disubstituted-beta-carbolines: formation of gamma-carbolines - Kusurkar, Radhika S.; Alkobati, Nabil A. H.; Gokule, Anita S.; Puranik, Vedavati G. (Tetrahedron, 2008)
Microwave-assisted conjugate addition of indole on nitro-olefins furnished nitro compounds, which were reduced to tryptamines. Further, by using Pictet-Spengler condensation, new 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines were synthesized in diastereoselective manner. Dehydrogenation of the tetrahydro-beta-carbolines produced new 1,4-disubstituted-beta-carbolines. As a new observation, in some of the cases, Pictet-Spengler condensation and dehydrogenation gave two products, namely 1,4-disubstituted-beta-carbolines and 1,4-disubstituted-gamma-carbolines. A mechanism is proposed for this observation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3; 4-Disubstituted-1; 4-disubstituted-beta-carboline; 4-disubstituted-gamma-carboline; 4-tetrahydro-beta-carboline; 4-tetrahydro-gamma-carboline; Pictet-Spengler reaction

Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide

Diastereoselective synthesis of 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines via glacial acetic acid catalyzed pictet - spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Arkivoc, 2011)
The Pictet-Spengler reaction of substituted tryptamines with cyclic ketones using glacial acetic acid afforded only one diastereomer of unreported 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines. The stereoselectivity in the reaction has been demonstrated using unsymmetrical ketones and single-crystal X-ray analysis of one of the spiro products in the form of base, its sulfate and hydrochloride salts, which indicated the formation of only the R, R diastereomer.
Keywords: 1; 3; 4; 4-Trisubstituted-2; 9-tetrahydrospiro-beta-carbolines; beta-substituted tryptamine; Diastereoselective Pictet-Spengler reaction; Glacial acetic acid

New poly(1,3,4-oxadiazole)s bearing pentadecyl side chains: synthesis and characterization - More, Arvind S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2012)
The 4-[4'-(Hydrazinocarbonyl)phenoxy]-2-pentadecylbenzohydrazide was polycondensed with aromatic diacid chlorides viz., terephthalic acid chloride (TPC), isophthalic acid chloride (IPC), and a mixture of TPC : IPC (50 : 50 mol %) to obtain polyhydrazides which on subsequent cyclodehydration reaction in the presence of phosphoryl chloride yielded new poly(1,3,4-oxadiazole)s bearing flexibilizing ether linkages and pentadecyl side chains. Inherent viscosities of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 0.530.66 dL g(-1) and 0.490.53 dL g(-1), respectively, indicating formation of medium to reasonably high molecular weight polymers. The number average molecular weights (M-n) and polydispersities (M-w/M-n) of poly(1,3,4-oxadiazole)s were in the range 14,660-21,370 and 2.22.5, respectively. Polyhydrazides and poly(1,3,4-oxadiazole)s were soluble in polar aprotic solvents such as N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, and N,N-dimethylformamide. Furthermore, poly(1,3,4-oxadiazole)s were also found to be soluble in solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, and m-cresol. Transparent, flexible, and tough films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from N,N-dimethylacetamide and chloroform solutions, respectively. Both polyhydrazides and poly(1,3,4-oxadiazole)s were amorphous in nature and formation of layered structure was observed due to packing of pentadecyl chains. A decrease in glass transition temperature was observed both in polyhydrazides (143-166 degrees C) and poly(1,3,4-oxadiazole)s (90-102 degrees C) which could be ascribed to internal plasticization effect of pentadecyl chains. The T-10 values, obtained from TG curves, for poly(1,3,4-oxadiazole)s were in the range of 433-449 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 124:1281-1289, 2012
Keywords: 3; 4-oxadiazole)s; Cashew nut shell liquid; pentadecyl; poly(1; polyhydrazides; thermal stability

Thermal stability of cellulose and their nanoparticles: Effect of incremental increases in carboxyl and aldehyde groups - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Oxidized cellulose containing carboxyl and aldehyde functional groups represent an important class of cellulose derivatives. In this study effect of incrementally increasing COOH and CHO groups at C2, C3, and C6 positions of cellulose and nanocellulose has been investigated, with a view to understanding their effect on thermal treatment of cellulose. The results show that 2,3-dialdehyde cellulose (DAC) is the most thermally stable oxidized product of cellulose while the most unstable derivatives contain carboxyl group at the C6 position (6CC). Carboxymethylcellulose (CMC), with carboxymethyl group on C6 position, is more stable than 6CC. Multi-functionalized celluloses 2,3,6-tricarboxycellulose and 6-carboxy-2,3-dialdehyde, have the same level of thermal stability as 6CC, showing that the presence of carboxyl at the C6 is a key destabilizing factor in the thermal stability of oxidized cellulose products. More the number of reducing end groups on the polymer chain, lower the thermal stability of the cellulose, as proved by comparing the TGA/DTG of monomeric analogs dextrose, cellobiose and glucuronic acid with the oxidized celluloses. The thermal stability trend observed for oxidized celluloses was DAC > DCC > nanoparticles > dextrose >glucuronic acid, caused by extent of reducing ends and COOH groups. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 2; 3; 3-Dialdehyde cellulose; 6-Carboxycellulose; 6-Tricarboxycellulose; cellulose; TGA/DTG

Molecular sieves and ultrasound-assisted synthesis of novel 1,3,4-oxadiazole-2-thiones derivatives as potential antifungal agents - Nikalje, Anna Pratima G.; Nimbalkar, Ms Urja D.; Tupe, Santosh; Vazquez, Julio A. Seijas; Tato, Maria Pilar Vazquez (19TH INTERNATIONAL ELECTRONIC CONFERENCE ON SYNTHETIC ORGANIC CHEMISTRY, 2015)
In the category of microorganism, fungi are considered as the special class of microbes responsible for opportunistic pathogenic infections in humans species. Due to the side effects of commercially available antifungal drugs and the emergence of new drug resistant fungal species in the past few years, has forced the researchers to search for novel and efficient antifungal drug molecules. The 1,3,4-oxadiazoles scaffold is associated with diverse biological activities. The multipurpose use of the Mannich bases in pharmaceutical chemistry promote us to prepare a new series of 5-(4-(benzyloxy)substituted phenyl)-3-((phenyl amino)methyl)-1,3,4oxadiazole-2(3H)-thione as antifungal agents. Herein, we report molecular sieves and ultrasound assisted synthesis of novel series of Mannich bases of the 5-substituted 1,3,4-oxadiazole-2-thiones by amino methylation with paraformaldehyde and substituted primary / secondary amines and their evaluation for antifungal activity. The structures of the newly synthesized compounds were determined by IR, NMR and Mass spectral study. The synthesized compounds exhibited interesting moderate to excellent antifungal activity against Candida albicans (NCIM 3557), Candida albicans(NCIM3471), Candida glabrata(NCIM3237), Cryptococcus neoformans (NCIM 3542), Cryptococcus neoformans(NCIM 3378), Aspergillus fumigates(NCIM 902), Aspergillus niger(NCIM 628) using Flucanazole as a standard reference drug. The synthesised compounds 6d, 6f,6g, 6h and 6j exhibited promising antifungal activity as antifungal agents.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular sieves; Ultrasound -assisted

Synthesis, antioxidant, anti-inflammatory, and antimicrobial screening of newer thiophene-fused arylpyrazolyl 1,3,4-oxadiazoles - Mahajan, Pravin S.; Nikam, Mukesh; Chate, Asha; Nimbalkar, Urja; Patil, Vrushali; Bobade, Anil; Chaudhari, Abhay; Deolankar, Dattatray; Javale, Balasaheb; Gill, Charansingh H. (Phosphorus Sulfur and Silicon and the Related Elements, 2015)
A series of newer 1,3,4-oxadiazole derivatives 3a-h, 5a-h containing a thiophene fused with pyrazole moiety of pharmacological significance have been synthesized. The compounds were characterized by H-1 NMR, IR, and mass spectral techniques. The compounds were screened for their in vitro antioxidant, anti-inflammatory and antimicrobial activities. Among them, Compounds 3b (EC50-14.98) and 3f (EC50-12.21) showed significant antioxidant activity. Compound 3a (EC50-15.23) showed good anti-inflammatory activity. Compound 3d was found as the most active derivative against bacterial and fungal strains.
Keywords: 1; 3; 4-Oxadiazole; Anti-inflammatory; Antimicrobial; Antioxidant; EC50; Thiophene-fused pyrazole

Synthesis and antitubercular activity of new 1,3,4-oxadiazoles bearing pyridyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Bhosle, Manisha R.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of more potent and safe new antitubercular agents, here new 2-pyridinyl substituted thiazolyl-5-aryl-1,3,4-oxadiazoles (6a-o), have been designed and synthesized using thionicotinamide as a starting, following novel multistep synthetic route. An intermediate, pyridinyl substituted thiazolyl acid hydrazide (4) when condensed with benzoic acids/nicotinic acids (5a-o) in the presence of silica supported POCl3 yielded better to excellent yields of the title compounds. All the synthesized compounds (6a-o) and intermediate acid hydrazide (4) have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG. Amongst them, 6f, 6j, 6l and 6o have revealed promising activity against M. bovis BCG at concentrations less than 3 mu g/mL. These compounds have shown low cytotoxicity (CC50: > 100 mu g/mL) towards four human cancer cell lines. Molecular docking study has also been performed against mycobacterial enoyl reductase (InhA) enzyme to gain an insight into the binding modes of these molecules and recorded good binding affinity. The ADME properties the title products have also been analyzed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Molecular docking; Pyridine; Thiazole

Synthesis, biological evaluation and molecular docking study of some novel indole and pyridine based 1,3,4-oxadiazole derivatives as potential antitubercular agents - Desai, N. C.; Somani, Hardik; Trivedi, Amit; Bhatt, Kandarp; Nawale, Laxman; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2016)
A series of indole and pyridine based 1,3,4-oxadiazole derivatives 5a-t were synthesized and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG both in active and dormant state. Compounds 5b, 5e, 5g and 5q exhibited very good antitubercular activity. All the newly synthesized compounds 5a-t were further evaluated for antiproliferative activity against HeLa, A549 and PANC-1 cell lines using modified MTT assay and found to be noncytotoxic. On the basis of cytotoxicity and MIC values against Mycobacterium bovis BCG, selectivity index (SI) of most active compounds 5b, 5e, 5g and 5q was calculated (SI = GI(50)/MIC) in active and dormant state. Compounds 5b, 5e and 5g demonstrated SI values >= 10 against all three cell lines and were found to safe for advance screening. Compounds 5a-t were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards MTB. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of enoyl reductase (InhA), which in turn helped to establish a structural basis of inhibition of mycobacteria. The potency, low cytotoxicity and selectivity of these compounds make them valid lead compounds for further optimization. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Indole; Molecular docking; Pyridine

Synthesis, biological valuation, and QSAR studies of novel pyrazole bearing pyridyl oxadiazole analogues as potential antimicrobial agents - Desai, N. C.; Kotadiya, G. M.; Trivedi, A. R.; Khedkar, Vijay M.; Jha, Prakash C. (Medicinal Chemistry Research, 2016)
A new series of 1-(2-(3-(4-nitrophenyl)-1-phenyl-1H-pyrazol-4-yl)-5-(pyridin-4-yl)-1,3,4 -oxadiazol-3(2H)-yl)-3-(aryl)prop-2-en-1-ones (5a-l) were synthesized by a simple and efficient synthetic protocol. The newly synthesized compounds were characterized by IR, H-1 NMR, C-13 NMR and Mass spectroscopy. The resulting structural diversity was screened for its antimicrobial activity the following bacterial and fungal strains: two Gram-positive bacteria [Staphylococcus aureus (MTCC-96), Streptococcus pyogenes (MTCC-442)], two Gram-negative bacteria [Escherichia coli (MTCC-443), Pseudomonas aeruginosa (MTCC-1688)] and three fungal species (C. albicans, A. niger and A. clavatus). Following this, in vitro cytotoxicity activity against HeLa cell lines was measured by MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide] assay. The observations derived from the diverse assays were utilized for building classification models based on a binary QSAR approach termed recursive partitioning (RP) analysis to probe the physic-chemical properties influencing the SAR for molecules. The decision tree derived from RP analysis could highlight structural characteristics that discriminate the actives from inactives which can serve as guide to design molecules with improved potency. In silico ADME predictions were performed to gauge their pharmacokinetic, safety and drug likeness profile.
Keywords: 1; 3; 4-Oxadiazole; Antimicrobial activity; Cytotoxicity; Pyrazole; Pyridine; QSAR

Ultrasound- and molecular sieves-assisted synthesis, molecular docking and antifungal evaluation of 5-(4-(benzyloxy)-substituted phenyl)-3-((phenylamino)methyl)-1,3,4-oxadiazole-2(3H)-thiones - Nimbalkar, Urja D.; Tupe, Santosh G.; Seijas Vazquez, Julio A.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nikalje, Anna Pratima G. (Molecules, 2016)
A novel series of 5-(4-(benzyloxy) substituted phenyl)-3-((phenyl amino) methyl)-1,3,4-oxadiazole-2(3H)-thione Mannich bases 6a-o were synthesized in good yield from the key compound 5-(4-(benzyloxy) phenyl)-1,3,4-oxadiazole-2(3H)-thione by aminomethylation with paraformaldehyde and substituted amines using molecular sieves and sonication as green chemistry tools. The antifungal activity of the new products was evaluated against seven human pathogenic fungal strains, namely, Candida albicans ATCC 24433, Candida albicans ATCC 10231, Candida glabrata NCYC 388, Cryptococcus neoformans ATCC 34664, Cryptococcus neoformans PRL 518, Aspergillus fumigatus NCIM 902 and Aspergillus niger ATCC 10578. The synthesized compounds 6d, 6f, 6g, 6h and 6j exhibited promising antifungal activity against the tested fungal pathogens. In molecular docking studies, derivatives 6c, 6f and 6i showed good binding at the active site of C. albicans cytochrome P450 enzyme lanosterol 14 alpha-demethylase. The in vitro antifungal activity results and docking studies indicated that the synthesized compounds have potential antifungal activity and can be further optimized as privileged scaffolds to design and develop potent antifungal drugs.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular docking; Molecular sieves; Ultrasound

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles

Synthesis, characterization and electrochemical investigations of mixed-ligand copper(II)-organic supramolecular frameworks - Singh, Sandeep K.; Srivastava, Ashish Kumar; Srivastava, Krishna; Banerjee, Rahul; Prasad, Jagdish (Journal of Molecular Structure, 2017)
Two mixed-ligand copper(II)-organic coordination compounds with 5,5'-dimethyl-2,2'-bipyridine (5,5'-Me(2)bpy) as a primary ligand while aliphatic malonate (Hmal) and aromatic 2-hydroxynicotinate (2-OHNA) as secondary ligands, were synthesized. These complexes are formulated as: [Cu(Hmal)(5,5'-Me(2)bPY)(H2O)](ClO4) 1 and [Cu-2(2-OHNA)(2)(5,5'-Me(2)bpy)(2)(NO3)KNO3) 2. These two complexes were structurally characterized by single crystal X-ray diffraction analysis. Characterization was further supported by powder X-ray diffraction analysis, elemental analyses, FT-IR, FAB-MASS and TGA, DSC studies. Cyclic voltammetric and UV-visible spectral studies of these two complexes have also been done. The electrochemical studies of complex 1 in DMSO and DMF have shown that this complex undergoes quasi reversible diffusion-controlled one-electron transfer reaction without any chemical complication while complex 2 in DMSO undergoes quasi-reversible diffusion-controlled one electron transfer reaction, following EC mechanism. The electrochemical behaviour of complex 2 in DMF is complicated probably due to presence of more than one species in solution phase. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 2 '-bipyridine; 3; 5; 5 '-dimethyl-2; 5-Tricarboxylic acid; Benzene-1; classification; Co-ordination-Compounds; Crystal-structures; cyclic voltammetry; magnetic properties; metal organic framework; Mixed-ligand complex; pi-pi stacking interaction; Polymers; Secondery Building Unit; Structural data; Supramolecular framework; Ternare Komplexe; X-ray diffraction

Design, synthesis, and pharmacological evaluation of fluorinated azoles as anti-tubercular agents - Gholap, Somnath; Tambe, Macchindra; Nawale, Laxman; Sarkar, Dhiman; Sangshetti, Jaiprakash; Damale, Manoj (Archiv Der Pharmazie, 2018)
Design, synthesis, and biological screening of 2,2-dimethyl-2,3-dihydrobenzofuran tethered 1,3,4-oxadiazole derivatives as anti-tubercular agents were described. The synthesis of the target compounds was conducted by a series of reaction schemes. All the synthesized compounds were characterized by IR, H-1 NMR, C-13 NMR, and mass spectrometry. The therapeutic potential of the synthesized compounds was confirmed by molecular docking studies. Among the synthesized compounds, 12a, 12c, 12d, 12e, 12g, and 12j were found to be more active against non-replicating than against replicating cultures of Mycobacterium tuberculosis H37Ra ex vivo and in vitro. These compounds exhibit minimum inhibitory concentration (MIC) values in the range of 2.31-23.91g/mL. The cytotoxicity study was conducted against the cell lines THP-1, A549 and PANC-1, and the compounds were observed to be non-toxic to host cells. Molecular docking was conducted with InhA (FabI/ENR) and suggested the antimycobacterial potential of the synthesized compounds. The investigation presented here was found to be adventitious for the development of new therapeutic agents against Mycobacterium infection.
Keywords: 1; 2; 2-dimethyl-2; 3; 3-dihydrobenzofuran; 4-Oxadiazole; anti-tubercular agents; Cytotoxicity; Molecular docking

One pot synthesis and biological evaluation of some new pyridine-3,5-dicarbonitrile derivatives - Joshi, Hitendra; Shah, Nirav; Sakar, Dhiman; Desai, N. C.; Jadeja, Krunalsinh A. (ChemistrySelect, 2018)
We have developed eco-friendly route for the synthesis of title compounds by using simple compounds like aromatic aldehydes, malononitrile, 4-bromothiophenol and NaHCO3. In continuation to this, a series of pyridine-3,5-dicarbonitriles were synthesized with excellent yields and assessed for their invitro antitubercular and antimicrobial activity. The results of the antimicrobial study showed potent antimicrobial activity as compared to the standard drugs (Chloramphenicol and Griseofulvin). It was noticed that the presence of electron donating groups significantly increases the antibacterial activity of the newly synthesized compounds. The title compounds further evaluated for antitubercular activity and from the promising results, they were found to possess significant biological activity against M. tuberculosis.
Keywords: 3; 4-Arylpyridine; 5-dicarbonitriles; Antimicrobial; Antitubercular; Catalyst

Synthesis of new 1,3,4-oxadiazole and benzothiazolylthioether derivatives of 4-arylmethylidene-3-substituted-isoxazol-5(4H)-one as potential antimycobacterial agents - Chavan, Abhijit P.; Deshpande, Rujuta R.; Borade, Nandkumar A.; Shinde, Abhijit; Mhaske, Pravin C.; Sarkar, Dhiman; Bobade, Vivek D. (Medicinal Chemistry Research, 2019)
A new series of 4-[(substituted benzylidene)-3-[(5-(pyridine-4-yl)-1,3,4-oxadiazole-2-ylthio)-methyl]i soxazol-5(4H)-one (6a-g) and 4-(substituted benzylidene)-3-((benzo[d]thiazol-2-ylthio)methyl)isoxazol-5(4H)-one (8a-g) was synthesized. All the synthesized compounds were screened for antitubercular activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) and antibacterial activity against Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162). Amongst the synthesized 1,3,4-oxadiazole and benzothiazoyl thioether derivatives, compounds 6b and 8b showed excellent antimycobacterial activity and compounds 6b, 8a, 8b, and 8d showed excellent antibacterial activity against all tested antibacterial strains. The synthesized compounds were further evaluated for their cytotoxic activity against the HCT 116 and HeLa cancer cell lines. The 1,3,4-oxadiazole and benzothiazoyl thioether derivatives 6a-g and 8a-g did not show cytotoxicity.
Keywords: 1; 3; 4-Oxadiazole; antibacterial activity; Antitubercular activity; Benzothiazol; Isoxazol-5(4H)-one; Thioeteher

Synthesis of novel of 2, 5-disubstituted 1, 3, 4-oxadiazole derivatives and their in vitro anti-inflammatory, anti-oxidant evaluation, and molecular docking study - Kashid, Bharat B.; Salunkhe, Pravin H.; Dongare, Balasaheb B.; More, Kishor R.; Khedkar, Vijay M.; Ghanwat, Anil A. (Bioorganic & Medicinal Chemistry Letters, 2020)
A series of novel 2, 5-disubstituted 1, 3, 4-Oxadiazole derivatives as a potential anti-inflammatory, and antioxidant agent were synthesized via cyclisation. Hydrazide molecule treated with substituted acids in the presence of phosphorus oxychloride (POCl3) as an efficient reagent as well as solvent by conventional method with shorter reaction time and excellent yield. The newly synthesized 1, 3, 4-oxadiazole derivatives exhibited excellent to good anti-inflammatory and anti-oxidant activities compaired to the standard drugs. Molecular docking study on the crucial anti-inflammatory target-cyclooxygenase-2 (COX-2) revealed the ability of the scaffold to correctly recognize the active site and achieve significant bonded and non-bonded interactions with key residues therein. This study could identify potential compounds which can be pertinent starting points for structure-based drug design to obtain newer anti-inflammatory agents.
Keywords: 1; 3; 4-Oxadiazole; Anti-inflammatory; Anti-Oxidant; Biological activity; computational chemistry

Visible-light-induced controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines for the synthesis of 3,4-dihydroisoquinolin-1(2h)-ones and isoquinolin-1(2H)-ones - Bansode, Ajay H.; Suryavanshi, Gurunath (Advanced Synthesis & Catalysis, 2021)
A visible light-rose bengal-TBHP mediated, controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines is developed for the synthesis of 3,4-dihydroisoquinolin-1(2H)-ones and isoquinolin-1(2H)-ones. The present method feature's a broad substrate scope, good functional group tolerances, and the products were prepared in good to excellent yields. The developed methodology further demonstrated in the synthesis of isoindolo[2,1-b] isoquinolin-5(7H)-one (topoisomerase-I inhibitor).
Keywords: 2; 3; 4-Dihydroisoquinolin-1(2H)-one; 4-tetrahydroisoquinolines; Isoquinolin-1(2H)-one; N-substituted 1; Oxidation; Photocatalysis

Synthesis, crystal structure and Hirshfeld surface analysis of a zinc(II) coordination polymer of 5-phenyl-1,3,4-oxadiazole-2-thiolate - Pirimova, Mehribon; Torambetov, Batirbay; Kadirova, Shakhnoza; Ziyaev, Abdukhakim; Gonnade, Rajesh G.; Ashurov, Jamshid (Acta Crystallographica Section E Crystallographic Communications, 2022)
A new zinc coordination polymer with 5-phenyl-1,3,4-oxadiazole-2-thiolate, namely, catena-poly[zinc(II)-bis(μ2-5-phenyl-1,3,4-oxadiazole-2-thiolato)-κ2N3:S;κ2S:N3], [Zn(C8H5N2OS)2]n, was synthesized. The single-crystal X-ray <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/D01712.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">diffraction analysis shows that the polymeric structure crystallizes in the centrosymmetric monoclinic C2/c <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group. The ZnII atom is coordinated to two S and two N atoms from four crystallographically independent (L) ligands, forming zigzag chains along the [001] direction. This polymer complex forms an eight-membered [Zn–S–C–N–Zn–S–C–N] chair-like ring with two ZnII atoms and two ligand molecules. On the Hirshfeld surface, the largest contributions come from the short contacts such as <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces, including H⋯H, C⋯H and S⋯H. Interactions including N⋯H, O⋯H and C⋯C contacts were also observed; however, their contribution to the overall stability of the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Lattice" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal lattice is minor.
Keywords: 3; 4-oxadiazole-2-thiol; coordination polymer; Hirshfeld surface analysis; crystal structure; zinc complex; 5-phenyl-1

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free